RP Experimental Method for the Design of Open-Graded Asphalt Mixes - Rioja, Héctor (2025)
This work describes the "RP" test, developed in Chile, which, in summary, consists of measuring the resistance to penetration under controlled temperature and speed conditions in open-graded asphalt mix specimens manufactured with varying binder contents. The optimal mix is considered to be the one that exhibits the highest resistance to penetration. The influence of temperature, aggregate characteristics, and type of binder falls outside the scope of this study. The "RP" method is parametric and empirical in nature and is currently in an exploratory stage.